Implementasi Ruhul Islam terhadap Pembentukan Karakter Mahasiswa di Perguruan Tinggi Berbasis Islam dan Teknologi Informasi - Mochamad Malik Akbar Rohandi; Helmi Aziz; Nadri Taja; Tia Yuliawati; Maudina Putri Giraliyandi; Hani Sutina (Ta'allum: Jurnal Pendidikan Islam, 2017)
Ruhul Islam is the core spirit of Islam that is the identity or characteristic of an individual or Islamic institution that has a mental attitude. It always guided by morals, according to the guidance of Islamic teachings so that can create a brotherhood of fellow Muslims in bringing people to a better state. The objective of this research is to know the comparison of Ruhul Islam application level to the embedded character in college student based on Islam and technology. Explanatory research method used primary data of field observation and questionnaire and secondary data, sample using Slovin formula and purposive sampling method with error rate of 10%, interconnection between variables using path analysis. Characteristics of respondents majority of women, active age 18-21 year students, high school graduates and the origin of UNISBA students 67% of Bandung while Telkom 82% outside Bandung. Implementation of Islamic values ​​with character formation in Islamic universities has a stronger relationship than information technology-based colleges with a R2 level of 37% versus 32.8%, more than 60% character formation can be influenced by other factors or variables.